Antidiarrheal Activity of Ethanolic Extract of Melochia corchorifolia L. and Glochidion thomsonii in Experimental Animal Models (Bangladesh Pharmaceutical Journal, 2019)
Diarrhoea is a public health problem in developing countries. It is therefore important to identify plants with antidiarrhoeal activity. Melochia corchorifolia and Glochidion thomsonii have been used in folk medicine to alleviate several diseases. The present study was performed to investigate the anti-diarrheal properties of ethanolic extract of M. corchorifolia whole plant and G. thomsonii bark. Anti-diarrheal potential was evaluated using castor oil and MgSO4 induced diarrhea, GI motility test as well as castor oil induced enteropooling assay in mice. Extracts were used at 250 and 500 mg/kg per orally. Loperamide (10 mg/kg p.o) was used as standard drug. The ethanolic crude extracts exhibited statistically significant and dose-dependent (250 and 500 mg/kg) anti-diarrheal effect against the total number of episodes of defecation as well as diarrheal feces. In animals pretreated with MC and GT extract showed 42.53% (p